2013
DOI: 10.1016/j.chom.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Bone Loss by Pathobiont-Mediated Nod1 Signaling in the Oral Cavity

Abstract: Summary Periodontitis is a common disease that is characterized by resorption of the alveolar bone and mediated by commensal bacteria that trigger host immune responses and bone destruction through unidentified mechanisms. We report that Nod1, an innate intracellular host receptor for bacterial peptidoglycan-related molecules, is critical for commensal-induced periodontitis in a mouse model. Mice lacking Nod1 exhibit reduced bone resorption as well as impaired recruitment of neutrophils to gingival tissues and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
196
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(209 citation statements)
references
References 25 publications
12
196
0
1
Order By: Relevance
“…This is consistent with earlier in vitro studies using the HEK293T cell reporter assay, revealing that soluble A. actinomycetemcomitans PGN and heat-killed cells of this species act as potent inducers of both NOD1 and NOD2 (42). Conversely, another recent report using the same cell-based reporter assay suggested that the tested A. actinomycetemcomitans strain mainly triggered NOD1 (44). The reason(s) for this discrepancy is not known; however, A. actinomycetemcomitans straindependent differences cannot be excluded, as the latter study, in contrast to the others, used strain JP2, which produces high levels of leukotoxin (47).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with earlier in vitro studies using the HEK293T cell reporter assay, revealing that soluble A. actinomycetemcomitans PGN and heat-killed cells of this species act as potent inducers of both NOD1 and NOD2 (42). Conversely, another recent report using the same cell-based reporter assay suggested that the tested A. actinomycetemcomitans strain mainly triggered NOD1 (44). The reason(s) for this discrepancy is not known; however, A. actinomycetemcomitans straindependent differences cannot be excluded, as the latter study, in contrast to the others, used strain JP2, which produces high levels of leukotoxin (47).…”
Section: Discussionsupporting
confidence: 91%
“…This was demonstrated in a recent study in which NOD1 was found to be essential for bone loss in a mouse ligatureinduced periodontitis model (44). Interestingly, this observation was linked to the identification of an A. actinomycetemcomitanslike (Ͼ60% coding sequence identity) mouse commensal (termed NI1060) which accumulated at the site of ligature placement and acted as a significant NOD1 activator (44). Based on these observations, it was proposed that NI10160, and possibly the human pathogen A. actinomycetemcomitans, can trigger bone loss via stimulation of NOD1 (44).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…The level of P. gingivalis infection in the mice treated with clodronate liposomes was decreased to 7-12%, and these animals exhibited the lowest amount of alveolar bone resorption. Hence, these results help to explain the important nexus between pathogen and inflammation, because they suggest that inflammation is an important component of the host-biofilm interaction for the emergence of the pathobiont that dysregulates the host response to produce dysbiosis and alveolar bone resorption (8,9,106). The predominance of the M1 macrophage phenotype in gingival tissue after P. gingivalis infection in the current study suggests that P. gingivalis may promote a dysregulated inflammatory response orchestrated by M1 macrophages.…”
Section: Figuresupporting
confidence: 56%